2021
DOI: 10.21608/ejaj.2021.195928
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Native Entomopathogenic Nematode Isolates for the Management of Selected Insect Pests in Nigeria

Abstract: Native entomopathogenic nematodes (EPNs) were evaluated for the management of three selected pests, Sesamia calamistis, Spodoptera frugiperda and Rhynchophorus ferrugineus in laboratory bioassays. The EPNs were isolated from soils from various locations within Ibadan, Nigeria using the greater wax moth (Galleria mellonella) as insect bait. A two-factor laboratory experimental assay was laid out in a completely randomized design and replicated three times. The EPN suspension was applied on insect larvae with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Red Palm Weevil (RPW), Rhynchophorus ferrugineus (Coleoptera: Curculionidae), is obnoxious to stem tissues of oil palm trees in West Africa. In Nigeria, Ottun et al (2021) inoculated larvae of R. ferrugineus with native Heterorhabitis sp. and observed that 84% of the pest died after 9 days post-inoculation.…”
Section: Potential Benefits Of Epn In Ssamentioning
confidence: 99%
“…Red Palm Weevil (RPW), Rhynchophorus ferrugineus (Coleoptera: Curculionidae), is obnoxious to stem tissues of oil palm trees in West Africa. In Nigeria, Ottun et al (2021) inoculated larvae of R. ferrugineus with native Heterorhabitis sp. and observed that 84% of the pest died after 9 days post-inoculation.…”
Section: Potential Benefits Of Epn In Ssamentioning
confidence: 99%
“…Elsewhere, in the complex of biological control agents, entomopathogenic fungi appear to be more effective and most successfully utilized insect pathogen, especially in the genera Aspergillus , Beauvaria , Metarhizium and Lecanicillium [ 83 ]. Preliminary work by Ottun et al, [ 84 ] revealed that there is great potentialfor the possibility of using entomopathogenic nematodes in the management of insect pests in Nigeria.…”
Section: Management Of Insect Pests Of Vegetable Cropsmentioning
confidence: 99%